2018
DOI: 10.1177/0961203318762604
|View full text |Cite
|
Sign up to set email alerts
|

Incremental health care services and expenditures associated with depression among individuals with cutaneous lupus erythematosus (CLE)

Abstract: Objectives The objective of this paper is to describe the annual direct medical expenditures for cutaneous lupus erythematosus (CLE) patients, and to estimate the incremental health care expenditures and utilization associated with depression among adults with CLE, while controlling for covariates. Methods Using the 2014 Medical Expenditure Panel Survey (MEPS), we compared CLE patients with and without depression to determine differences in: (a) health care utilization-inpatient, outpatient, office-based and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…Nevertheless, researchers have been able to give reasons to some of the shortcomings present in the health-care sector in Nigeria. For instance, Ogunsanya et al (2018) [18] blamed Nigeria poor health performance to the fluctuating government revenue gotten from oil price. For instance, considering the country's budgetary allocation for health, the Federal Ministry of Health appropriation bill is 340.456 billion naira out of the total budget of 8.612 trillion naira in 2018 representing 3.95% of the total budget.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, researchers have been able to give reasons to some of the shortcomings present in the health-care sector in Nigeria. For instance, Ogunsanya et al (2018) [18] blamed Nigeria poor health performance to the fluctuating government revenue gotten from oil price. For instance, considering the country's budgetary allocation for health, the Federal Ministry of Health appropriation bill is 340.456 billion naira out of the total budget of 8.612 trillion naira in 2018 representing 3.95% of the total budget.…”
Section: Introductionmentioning
confidence: 99%
“…40 While depression has not been extensively studied in cross-sectional studies conducted in CLE patients, a qualitative study reported that self-reported depression was a concern for patients. 18 A plausible reason for the insignificance in the current study, despite the prevalence of depression in CLE 39,47 , is that depression is commonly underdiagnosed in other chronic diseases, 48 and is likely applicable to CLE. Current and past smoking histories have been linked to an increase in systemic vascular inflammatory processes such as IL-6, 49 which can worsen some symptoms and, subsequently, QoL.…”
Section: Discussionmentioning
confidence: 66%
“…The estimated average annual incremental cost for CLE was 10,119 USD in 2018. 17 The difficulties of being low income compounded with the financial, emotional and physical toll of having CLE likely result in poorer quality of life among low income patients with CLE.…”
Section: Discussionmentioning
confidence: 99%